An optimal early warning system for currency crises under model uncertainty - Mamdouh Abdelmoula Mohamed Abdelsalam; Hany Abdel-Latif (Central Bank Review (CBR), 2020)
This paper assesses several early warning (EWS) models of financial crises to propose a model that can predict the incidence of a currency crisis in developing countries. For this purpose, we employ the equal weighting (EW) and dynamic model averaging (DMA) approaches to combine forecast from individual models allowing for time-varying weights. Taking Egypt as a case study and focusing only on currency crises, our findings show that combined forecast (EW- and DMA-based EWS), to account for uncertainty, perform better than other competing models in both in-sample and out-of-sample forecasts.
Keywords: E44; F31; F47; G01; 330; Financial crises; Currency crises; Early warning; Uncertainty; Egypt